Three Promising Strains of Pennisetum Pedicellatum (Deenanath Grass) for Forage and Soil Conservation in Bihar - Mukerji, S.K.; Prasad, L.K. (Journal of Soil and Water Conservation, 2022)
The problem of grassland is acute in a thickly populated State like Bihar. Parts of the State carry a population of as much as 500 famished cattle and over a thousand people per square mile. All possible arable lands are cultivated for raising human-food. Only the relatively infertile lands are available for supporting pastures of self sown inferior grasses requiring low soil fertility. The forest or village pastures are usually over grazed by overwhelming cattle population getting some bite during the wetter part of the year. During the dry months such pastures hardly produce any appreciable forage and only the unpalatable species of grasses survive.